VARIABILIDADE GENÉTICA E OCORRÊNCIA DE BIÓTIPOS DE AZEVÉM COM SUSPEITA DE RESISTÊNCIA AO GLYPHOSATE NA REGIÃO DE GUARAPUAVA/PR E ESTRATÉGIAS TECNOLÓGICAS DE MANEJO - Ramos, Darwin Caleff (2015)
The work was performed in order to evaluate in Guarapuava region, Parana State, if there are resistant ryegrass biotypes to herbicides with different mechanisms of action; characterize the degree of genetic similarity between ryegrass accesses susceptible and resistant to glyphosate and verify the efficiency and quality of glyphosate application and ACCase inhibitors herbicide with adjuvant in desiccation management. Three experiments were conducted in field and laboratory conditions in Guarapuava County, Parana State, during 2013 and 2014 seasons, at Universidade Estadual do Centro Oeste - UNICENTRO. Treatments were disposed in randomized blocks design. In experiment 1, it was used a factorial scheme in field conditions 5 x 3 + 1, with 5 herbicides (glyphosate 4320 g ha?¹; iodosulfurom-methyl 7,5 g ha?¹; clethodim 192 g ha?¹; quizalofop-p-tefuril 240 g ha?¹ e paraquat 600 g ha?¹), three localitions (Unicentro, Entre Rios and Palmeirinha) and a check. In a second work a 3 x 2 + 1 factorial with 3 herbicide (glyphosate 4320 g ha?¹; iodosulfurom-methyl 7.5 g ha?¹; clethodim 192 g ha?¹; quizalofop-p-tefuril 240 g ha?¹ e paraquat 600 g ha?¹), three locations (Unicentro, Entre Rios and Palmeirinha) and a check. In a second work in factorial scheme 3 x 2 + 1 with 3 herbicides (glyphosate with 2160 and 4320 g ha?¹, iodosulfurom-methyl 12.5 and 25.0 g ha?¹, clethodim 192 and 384 g ha?¹), conducted under greenhouse conditions and natural environment, and a check. The presence of ryegrass resistant to glyphosate ryegrass was identified only in one of the locations (Unicentro, CEDETEG Campus). Paraquat, clethodim and quizalofop-p-tefuril herbicides efficiently controlled resistant ryegrass with suspected to glyphosate resistance, in Guarapuava region, Parana State. In experiment 2, resistant and susceptible plants were collected from locality containing resistant plants, being DNA evaluated by using ISSR seven markers (Inter Simple Sequence Repeat). It was observed genetic similarity of 34% between resistant ryegrass plants to glyphosate herbicide and 38% the susceptible ones. Results showed that there is moderate genetic diversity in resistant ryegrass population. In experiment 3, two studies were carried out in field and laboratory conditions, containing 12 treatments consisting by: glyphosate (1440 g ha?¹), clethodim (120 g ha?¹), quizalofop-p-tefuril (100 g ha?¹), glyphosate + clethodim (1440 + 120 g ha?¹), glyphosate + quizalofop-p-tefuril (1440 + 100 g ha?¹), associated to Assist® adjuvant (1.0 L ha?¹) and TA35® (0.1 L ha?¹), Glyphosate (1440 g ha?¹) associated to Orobor adjuvant N1® (0.1 L ha?¹) and a check without application. Tank mixtures of glyphosate with clethodim or quizalofop-p-tefuril or even clethodim or quizalofop-p-tefuril isolated were efficient in controlling ryegrass, highlighting the fast initial action of glyphosate + clethodim, regardless of used adjuvant. For all treatments have not been identified significant differences between frequency of total deposition or medium spraying in ryegrass leaves. The results suggest that the presence of these ACCase inhibitors herbicide (clethodim and quizalofop-p-tefuril) may influence over the increasing of spray deposition on ryegrass plants.